Chinese foreign direct investment in Europe follows conventional models - Christian Dreger; Margot Schüller (DIW Economic Bulletin, 2017)
This report examines China's strategy for investing in Europe. While investing in Western Europe is primarily about obtaining access to advanced technologies, investing in Central and Eastern Europe is more about establishing a presence in the EU common market and expanding infrastructure-which also fits into the framework of the New Silk Road Initiative. An econometric analysis reveals that the investments largely follow conventional explanatory patterns. If we distinguish between different forms of market access, the determinants become much more specific. A high industrial share, sound institutions, and unit labor costs in the target country all have a negative impact on investment in new ventures, but not on investment in existing companies. Differing investment patterns, as well as the heterogeneous interests of the EU member states, make it difficult to implement a coordinated response to the Chinese investment offensive. At the very least, however, a kind of reciprocity should be introduced within the framework of an investment protection agreement between the EU and China. This could reduce the growing skepticism surrounding Chinese investment activities.
Keywords: F21; E22; C25; 330; Chinese foreign investment strategy; knowledge and technology transfer; FDI determinants